Evolution of eruptive process at Sabancaya Volcano (Perù) 2014- 2018 - Apaza Choquehuayta, Fredy Erlingtton (2018)
Sabancaya Volcano (5960 m) is a stratovolcano located approximately 80 km southeast of the city of Arequipa in southern Peru. In the Holocene, activity at Sabancaya has included several Plinian eruptions which were followed by effusion of massive andesitic and dacitic lava flows that now cover large portions of the west, north and east flanks of the edifice. The Volcanological Observatory of INGEMMET (OVI) uses geophysical and geochemical monitoring techniques to track changes in activity at Sabancaya. The first precursors of the current eruptive crisis were detected in 2014, when a slight but visible increase in fumarolic emissions was observed. Around the same time, sulfur dioxide (SO2) emissions were detected for the first time. In 2015, volcano-tectonic and hybridfrequency earthquakes set in, and their frequency of occurrence increased throughout 2015 and into early 2016. Clearly, magma was rising towards the surface. Finally, on November 6, 2016, the volcano erupted with an explosive ash emission.